Assessment of the Influence of the Number of Layers on the Results of Reservoiment - Bobomurodov Utkir Ziyadullayevich (Scientific Trends, 2024)
Due to satellite oil gases, global warming, acid residues, climate change and the strengthening of the greenhouse effect are taking place. In fulfillment of the tasks defined by the Action Strategy for five priority areas of development of the Republic of Uzbekistan in 2017-2021, developed on the initiative of the President of the Republic of Uzbekistan Shavkat Mirziyoyev, the Uzbekneftgaz National Holding has adopted a program to increase hydrocarbon production for 2017-2021.
Keywords: Due to satellite oil gases, global warming, acid residues, climate change and the strengthening of the greenhouse effect are taking place. In fulfillment of the tasks defined by the Action Strategy for five priority areas of development of the Republic of Uzbekistan in 2017-2021, developed on the initiative of the President of the Republic of Uzbekistan Shavkat Mirziyoyev, the Uzbekneftgaz National Holding has adopted a program to increase hydrocarbon production for 2017-2021.